A PLS Approach to Measuring Investor Sentiment in Chinese Stock Market. (6th August 2017) - He, Gang; Zhu, Shuzhen; Gu, Haifeng
Abstract : We select five objective sentiment indicators and one subjective sentiment indicator to build investor sentiment composite index in Chinese stock market by using the partial least squares. The reason why we do that is to improve the shortcomings of the principal component analysis, which was adopted to build investor sentiment composite index in the pioneering research. Moreover, due to the large proportion of individual investors in Chinese stock market and the rapid change of investor sentiment, we innovatively use the weekly data with smaller information granularity and higher frequency. Through empirical tests for its reasonability and market's predictive capability, we find that this index appears to fit the data better and improves prediction.